The combination of motor imagery and post-activation performance enhancement is efficient to emphasize the effects of warm-up on sport-specific performance - Rumeau, V.; Grospretre, S.; Babault, N. (Journal of Sports Science & Medicine, 2024)
Motor imagery (MI) or post-activation performance enhancement (PAPE) have shown acute benefits for sports performance. The aim of the present study was to investigate the cumulative effects of MI and PAPE when combined within a warm-up routine. Ten men boxers participated in this study. They underwent four experimental sessions composed of a standardized warm-up followed by 1) maximal leg press extensions (CONTROL-PAPE), 2) mental imagery of force and sprint tasks (CONTROL-MI), 3) maximal leg press extensions followed by mental imagery of force and sprint tasks (PAPE-MI) and 4) mental imagery of force and sprint tasks followed by then maximal leg press extensions (MI-PAPE). Post-tests consisted of boxing reaction time, average and maximal boxing force, maximal handgrip strength, repeated sprint ability and the NASA-TLX fatigue questionnaire. No difference was obtained between PAPE-MI and MI-PAPE for the different measurements. Compared to CONTROL-PAPE and CONTROL-MI, both the PAPE-MI and MI-PAPE significantly enhanced boxing average force (P < 0.05) and repeated sprint ability (P < 0.01). Compared to CONTROL-PAPE, both the PAPE-MI and MI-PAPE increased boxing reaction time (P < 0.05), PAPE-MI increased the handgrip strength (P < 0.05) and MI-PAPE increased boxing maximal force (P < 0.01). Compared to CONTROL-MI, both the PAPE-MI and MI-PAPE increased boxing maximal force (P < 0.001), handgrip strength (0 < 0.01) and MI-PAPE increased boxing reaction time (P < 0.05). The NASA-TLX questionnaire was not affected by the warm-up modalities (P = 0.442). Combining PAPE-MI and MI-PAPE protocols within the warm-up produced cumulative positive effects on acute muscular performance without increasing subjective fatigue. PAPE-MI and MI-PAPE are both interesting modalities for optimizing warm-up routines.